GAMBARAN FUNGSI HATI DAN GINJAL PADA PENDERITA MALARIA - Darmawaty .; Fitriani M; Ruland DN Pakasi; Hardjoeno . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
the prevalence of malaria disease is still high in Indonesia. It requires to be diagnosed and handled quickly to decrease themorbidity and the mortality. the purpose of this study was to evaluate the results liver and kidney function tests of malaria patients forcomplications and to know the etiology. A cross sectional method was used for this study by using medical record of malaria patientsthat at Wahidin Sudirohusodo hospital in Makassar during January to December 2006. Malaria was diagnosed based on pheripheralblood while the examination of Sgot, SgPt (DgKC method), ureum (Barthelots method) and creatinine (Jaffe's method) were doneby chemistry autoanalizer. the increasing concentration of Sgot was found on 14 patients (42.4%) which was consisted of high at 12patients, SgPt on 13 patients (39.4%), ureum on 2 patients (6.1%) and creatinine on 11 patients (33.3%). Plasmodium falciparum wasfound on 18 patients (54.5%) and Plasmodium vivax on 15 patients (45.5%). the Sgot, SgPt, ureum, and creatinine concentrationsmostly exist in normal range, this indicated that liver and kidney damage was still mild. the etiology of malaria disease was Plasmodiumfalciparum and Plasmodium vivax, it was found from examination of pheripheral blood. there was no significant different in this studyfor the increasing of Sgot, SgPt, ureum and creatinine concentrations based on plasmodium etiology.